2014
DOI: 10.1111/acel.12225
|View full text |Cite
|
Sign up to set email alerts
|

Modulated expression of human peripheral blood microRNAs from infancy to adulthood and its role in aging

Abstract: Accumulating evidence suggests a role for microRNAs (miRNAs) in regulating various processes of mammalian postnatal development and aging. To investigate the changes in blood-based miRNA expression from preterm infants to adulthood, we compared 365 miRNA expression profiles in a screening set of preterm infants and adults. Approximately one-third of the miRNAs were constantly expressed from postnatal development to adulthood, another one-third were differentially expressed between preterm infants and adults, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 44 publications
3
23
0
Order By: Relevance
“…Profiling of miRNAs has been performed in whole blood 10 and PBMCs 28 of humans; in these studies, the majority of miRNAs were downregulated with age. In our study, 25 of 27 miRNAs selected as DERs from the whole blood using a 4-fold change criterion were decreased, similar to previous results observed in humans (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Profiling of miRNAs has been performed in whole blood 10 and PBMCs 28 of humans; in these studies, the majority of miRNAs were downregulated with age. In our study, 25 of 27 miRNAs selected as DERs from the whole blood using a 4-fold change criterion were decreased, similar to previous results observed in humans (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, microRNAs (miRNAs) have been investigated to identify how they modulate aging-associated signaling pathways by binding to specific promoter regions of target mRNAs 8, 9. To this end, differentially expressed miRNAs (DERs), originating from a specific fraction of blood, such as cells, serum, or microvesicles (e.g., exosomes), have been identified in adult blood compared to that of infancy,10, 11, 12 which could provide key molecules to elucidate the aging mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…There is significant variation in the expression of miRNA during aging. Genome-wide assessment of miRNA expression revealed that the majority of miRNAs decreased with age (131,132). Interestingly, host-derived miRNAs may also influence the composition of the gut microbiome (133).…”
Section: Microbiome and Agingmentioning
confidence: 99%
“…This stability occurs as miRNAs are released from cells to extracellular space in membrane vesicles (2) or bound to protein complexes (3,4). Alterations in miRNA levels in blood may reflect the changes during normal physiologic processes (5,6) and have been related to several pathologic conditions, including gynecologic diseases (7,8).…”
mentioning
confidence: 99%